Generation Z students' perceptions of the transformation of the auditor's role in Islamic-based auditing - Immanuel Felix Natanael Sinaga; Andreani Hanjani (Journal of Applied Business Administration, 2026)
This study investigates the influence of Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and Perceived Islamic Ethics on the transformation of the auditor’s role in the digital era from the perspective of Generation Z. A quantitative correlational approach with a cross-sectional design was employed. Data were collected from 344 accounting students at universities in Yogyakarta using proportional stratified sampling. The data were analyzed using multiple linear regression with SPSS. The findings show that all four independent variables exert positive and statistically significant effects on perceptions of the auditor’s role transformation in the digital context. The results of the study show an R-Square value of 0.788, which means that 78.8% of the variation in the transformation of the auditor's role in the digital era can be explained by the variables Perceived Usefulness, Perceived Ease of Use, Perceived Risk, and Perceived Islamic Ethics, while the remaining 21.2% is explained by other factors outside the model. Theoretically, this study extends the Technology Acceptance Model by incorporating Perceived Risk and Perceived Islamic Ethics, thereby enhancing its relevance in Islamic auditing contexts. Practically, the results highlight the importance of integrating digital competencies and Islamic ethical values into auditor education and supporting the development of Sharia-compliant digital auditing standards globally.